Correlates of Job Satisfaction of Community School’s Teachers of Phidim Municipality, Nepal - Bhandari, Laxmi Prasad Bhandari (Dristikon: A Multidisciplinary Journal, 2021)
Teachers' satisfaction is a significant concern of the overall education system of a country. This study examines the factors influencing job satisfaction of community school teachers' of Phidim Municipality. More specifically, this paper aims to investigate whether the sex of the teacher, income, nature of the job, age, birthplace, religion and educational status affect teachers' job satisfaction or not. This study is a cross sectional survey where sample size is determined by using Slovin's formula and the data were drawn from a self-administered questionnaire from randomly selected community school teachers. The percentages, Chi-Square test, and binomial logistic regression model were used for univariate, bivariate, and multivariate analysis using SPSS. The yearly income, age of teachers, and nature of job were found significantly associated with teachers' satisfaction under bivariate analysis whereas the binomial logistic regression justified the association of teachers' satisfaction to income of teachers and nature of their job only. The association of teacher's satisfaction to the sex of respondent, religion, educational status, and birthplace were found not significant using both bivariate and multivariate analysis. It is the conclusion that the permanency of job and reasonable salary must be managed mainly to make teacher's satisfied. In the present Nepalese context, the adjustment of teacher's salary as per the changing cost of living figure is necessary for teacher's job satisfaction. Likewise, the formulation of the teacher service commission as constitutional body, and regular operation of examination for teacher's permanent recruitment can enhance teacher's job satisfaction.